REKONDISI MESIN BUBUT DO ALL LT.13 DI LABORATORIUM MEKANIK POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Dimas Aditya; Rendi Warizki; Ariyanto; Zulfitriyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
In the production process, maintenance has an important role to ensure the smooth running of the production process. This machine maintenance scheduling discusses the process of restoring the initial condition (reconditioning) of the DoALL LT.13 lathe by focusing on repairs to the automatic system, non-functioning thread system and geometric testing. The method applied to overcome this problem is the observation method (5 whys). Stages Reconditioning starts from collecting initial damage data obtained from machine inspection, then continues with analyzing the damage, and taking corrective action based on the results of the analysis. Function testing methods, geometric testing, machine performance tests are carried out to see whether the reconditioning objectives have been achieved. Based on the test results after reconditioning, the data obtained by the automatic system function, the threaded system returns to normal, the average geometric deviation value is still within tolerance based on ISO standards. 1708 and machine performance tests resulting from turning workpieces are still considered normal based on the ISO 10816 standard.